2013
DOI: 10.1136/bcr-2013-009892
|View full text |Cite
|
Sign up to set email alerts
|

A rare presentation of cerebral venous sinus thrombosis associated with tubercular meningitis

Abstract: Central nervous system (CNS) tuberculosis may manifest as meningitis, meningoencephalitis, tuberculoma, tubercular abscess, stroke due to tuberculous vasculitis and tuberculous encephalopathy. Occasionally, tubercular meningitis (TBM) can predispose to cerebral venous sinus thrombosis (CVST). We report a young man, who developed CVST as a complication of TBM. Worsening of pre-existing headache, impairment of consciousness and seizures should raise suspicion of CVST in any patient with CNS infection. Early diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…TB meningitis accounts for about 1% of all cases of TB and 6% of all extrapulmonary infections in immunocompetent individuals 7. One of the uncommon sequelae of TB meningitis is septic dural sinus thrombosis as previously reported in a case by Verma et al 8. In another case, extensive calvarial TB causing compression and occlusion of the SSS was reported in a man presenting with a non-healing scalp sinus 9…”
Section: Discussionmentioning
confidence: 75%
“…TB meningitis accounts for about 1% of all cases of TB and 6% of all extrapulmonary infections in immunocompetent individuals 7. One of the uncommon sequelae of TB meningitis is septic dural sinus thrombosis as previously reported in a case by Verma et al 8. In another case, extensive calvarial TB causing compression and occlusion of the SSS was reported in a man presenting with a non-healing scalp sinus 9…”
Section: Discussionmentioning
confidence: 75%
“…7 Despite this high prevalence of TB in India, its association with CVT has been scarcely reported. 8 It should be kept in mind that CVT can also present with altered sensorium and other neurological manifestations. The other important causes for altered mental status in TB are tuberculous meningoencephalitis, tuberculoma, hydrocephalus and metabolic encephalopathies like hyponatremia.…”
Section: Discussion Of Managementmentioning
confidence: 99%
“…The postulated mechanisms of CVT in tuberculosis are: Endothelial injury due to the inflammatory response, sluggish venous flow, increased platelet aggregation and release of procoagulant factors. [21] Due to the lack of larger studies, it is difficult to establish if the co-occurrence of these two diseases is due to a chance association or it is causally related. If a patient has clinical features and signs suggestive of chronic meningitis along with the cerebrospinal fluid examination and neuroimaging findings suggesting the presence of TBM; or, if there is evidence of tuberculosis elsewhere, then the suspicion of concomitant TBM should arise in the clinician's mind.…”
Section: What Are the Etiological Factors For Cerebral Venous Thrombomentioning
confidence: 99%
“…Literature search on Medline with the key words of "CVT and tuberculosis" yielded only a few case reports. [19][20][21] Pai et al reported associated tuberculosis as an etiological factor for CVT in 14.3% of patients. [13] But the authors have not commented about the type of tuberculosis (whether it was TBM or pulmonary tuberculosis).…”
Section: What Are the Etiological Factors For Cerebral Venous Thrombomentioning
confidence: 99%